Factors related to the suppression of the antitumour immune response in female dogs with inflammatory mammary carcinoma. - Karine Araújo Damasceno; Aline Michelle Dos Santos-Conceição; Laís Pereira Silva; Thiago Marconi de Souza Cardoso; Carlos Humberto da Costa Vieira-Filho; Samantha Hellen Santos Figuerêdo; Emanoel Martins-Filho; Barbra Gabriela Oliveira de Faria; João Moreira da Costa-Neto; Geovanni Dantas Cassali; Alessandra Estrela-Lima (PLoS ONE, 2022)
Inflammatory mammary carcinoma (IMC), a neoplasia affecting women and female dogs, is considered an aggressive cancer with high metastatic potential and a low survival rate. Studies focused on the tumour microenvironment indicate that the aggressive behaviour of this tumour is primarily correlated with immunological factors as well as inflammation. The objective of this study was to analyse the possible strategies used by the tumour cells to suppress the immune response in female dogs with IMC. Forty-six female dogs were divided into three groups: control (C, n = 10), IMC (n = 14) and mammary carcinoma (MC, n = 22). Clinical-pathological evaluations, survival at follow-up, immunophenotyping of leukocytes in peripheral blood and tumours, and immunohistochemical evaluation of CD4+, granzyme B, perforin and FAS-L were performed. Clinical and pathological results showed a higher frequency of the primary form of neoplasia, solid arrays of tumor cells and a lower survival rate in the IMC group (30 days). Morphometric analysis of inflammatory infiltrate revealed more lymphocytes and macrophages in the IMC group. Immunophenotyping analysis of peripheral blood revealed a higher frequency of CD8+ T-cells (p = 0.0017), a lower frequency of CD4+ T-cells (p <0.0001), and significantly higher mean MHCI and MHCII CD14+ fluorescence intensity in the IMC group (p = 0.038 and p = 0.0117, respectively). The immunohistochemical evaluation of tumour sections showed fewer FAS-L-positive inflammatory cells in the IMC group. These results suggest the important contribution of CD8+ T-cells, macrophages and FAS-L in the aggressiveness of IMC.